2016
DOI: 10.2139/ssrn.2771042
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Up with the E-Joneses: Do Online Social Networks Raise Social Comparisons?

Abstract: Online social networks such as Facebook disclose an unprecedented volume of personal information amplifying the occasions for social comparisons. We test the hypothesis that the use of social networking sites (SNS) increases people's dissatisfaction with their income. After addressing endogeneity issues, our results suggest that SNS users have a higher probability to compare their achievements with those of others. This effect seems stronger than the one exerted by TV watching, it is particularly strong for yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
(53 reference statements)
5
20
0
3
Order By: Relevance
“…In both specifications the proxies of social capital are significantly and positively correlated with life satisfaction. This result is consistent with previous literature examining the role of relational goods in individual happiness (Becchetti et al, ; Sarracino, ; Bartolini et al, ; Bartolini and Sarracino, ).…”
Section: Partial Correlations Using Olssupporting
confidence: 93%
See 1 more Smart Citation
“…In both specifications the proxies of social capital are significantly and positively correlated with life satisfaction. This result is consistent with previous literature examining the role of relational goods in individual happiness (Becchetti et al, ; Sarracino, ; Bartolini et al, ; Bartolini and Sarracino, ).…”
Section: Partial Correlations Using Olssupporting
confidence: 93%
“…The author suggested that Internet access might raise material aspirations thereby worsening people's satisfaction with their income position. Based on Eurobarometer and on Italian MHS data, Sabatini and Sarracino () found that SNS users have a higher probability to compare their achievements to those of others, resulting in lower satisfaction with their income. Using a survey conducted on a representative sample of French Facebook users, Pénard and Mayol () showed that Facebook can interfere with subjective well‐being through its effects on self‐esteem.…”
Section: Sns and Well‐beingmentioning
confidence: 99%
“…The typical econometric strategy to tackle this has been to employ instrumental variables, which exploit some forms of exogenous variation that can explain Internet use differences among individuals. Examples of instrumental variables that have been used in this literature are broadband infrastructures in different regions (Hyll and Schneider, 2013;Bhuller et al, 2013;Sabatini and Sarracino, 2016;, the country's slope of terrain (that affects investments in Internet infrastructure; Ganju et al, 2015), and peer effects in ICT use (Penard et al, 2013;Castellacci and Viñas-Bardolet, 2017).…”
Section: An Overview Of the Literature On Internet And Well-beingmentioning
confidence: 99%
“…The emergence of SNSs may reinforce this tendency, as they display an unprecedented volume of personal information that can be a powerful source of social comparison (Sabatini and Sarracino, 2015). As suggested by Sabatini and Sarracino (2015), social comparison relies on the availability of information about the lives of others. SNSs offer a fertile environment for upward social comparison, which in turn can lead to envy and negative feelings (e.g., Krasnova et al, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%